Design and Implementation of a Smart Hand Sanitizer Dispenser with Door Controller using ATMEGA328P - Edozie, Enerst; Wantimba, Janat; Kalyankolo, Zaina (International Journal of Engineering and Information Systems, 2020)
In this covid-19 pandemic period which is a global outbreak, hand hygiene is the core preventive measure in the spread of the disease as advised by WHO (World Health Organization) which includes washing hands with water and soap regularly, hand sanitizing using hand sanitizers, etc. Hygiene refers to the practices conducive to maintaining health and preventing disease especially through cleanliness such as washing hands, coughing in the elbow etc. Hand washing helps to prevent any diseases that spread through contact. In order to eliminate most of the germs on the hands, one needs to apply a good hand washing practice. In most healthcare settings, alcohol-based hand sanitizers are preferable to hand washing with soap and water because it can be easily tolerated and it is also more effective at reducing bacteria. Hand sanitizer is a liquid, gel, or foam generally used to decrease infectious agents on the hands. A sanitizer is designed to kill germs on skin, objects and surfaces. This research paper aim to design and implement a low cost smart hand sanitizer dispenser with door controller based on ATMEGA328P (Microcontroller), electromagnetic lock and Ultrasonic sensor that can help to solve the challenges faced by security guards at different stations such as bank doors, school gates, hospital gates etc. in enforcing this hand sanitizing action before letting people in to where ever they intend to enter as some people are not willing to collaborate, some look at it as a wastage of their time and also sometimes these security guards can let some people in without sanitizing just because they are their friends or family relatives which is very risky. Therefore, the smart hand sanitizer is stationed at the entrance door and it is connected to the door in such a way that it controls it. That is to say, when a person(s) wants to access the entrance door, they must first sanitizer their hands or else the door will remain locked. With this smart hand sanitizer dispenser, an ultrasonic sensor is used to check the presence of hands below the outlet of the sanitizer machine. It will continuously calculate the distance between the sanitizer outlet and itself and tells the microcontroller to turn on the servo motor whenever the distance is less than 10cm to push the sanitizer out and immediately after the sanitizer outlet dropping some amount into your hands, the electromagnetic lock will de-energize (unlock the door) lighting up a green LED and display a word “The Entrance Door is Open” on the LCD display, then the second servo motor will open the entrance door. Otherwise, the door will neither unlock nor open but a red LED will continuously be on with the “Please Sanitize Here” words displayed on the LCD display.
Keywords: Hygiene, Hand sanitizer, Microcontroller, Ultrasonic sensor, Servo motor, LCD, Electromagnetic Lock.